2013
DOI: 10.4172/1747-0862.1000062
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of PCR-Based Detection Tests for Helicobacter Pylori in Otitis Media: A Meta-Analysis

Abstract: Background and objectives: Helicobacter pylori (H. Pylori) infection has serious consequences such as peptic ulcers and gastric cancer. Histologic identification of organisms remains the gold standard in the diagnosis of H. pylori. This meta-analysis reviewed the overall diagnostic accuracy of polymerase chain reaction (PCR) vs histology of H. pylori infection in the patients with otitis media with effusion (OME). Methods:Medline, Scopus and ISI web of science were systematically searched. Articles meeting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…A case in point is the vacA gene which is much associated with clarithromycin and tinidazole resistance and the cag A gene which is also associated with tinidazole resistance [ 61 ]. Strong association between amoxicillin resistance and the hop gene of the bacterium has been reported [ 62 ]. Ureases have been reported to be strongly associated with metronidazole resistance in the bacterium [ 63 ], while babA and babB genes have been implicated in the H. pylori erythromycin resistance [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…A case in point is the vacA gene which is much associated with clarithromycin and tinidazole resistance and the cag A gene which is also associated with tinidazole resistance [ 61 ]. Strong association between amoxicillin resistance and the hop gene of the bacterium has been reported [ 62 ]. Ureases have been reported to be strongly associated with metronidazole resistance in the bacterium [ 63 ], while babA and babB genes have been implicated in the H. pylori erythromycin resistance [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of our study group was 6.73±2. 16. In contrast, another study was done on a wider variety of ages, with a mean age of 25.6 years 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PCR is considered a rapid, sensitive, specific, low cost and useful method for detection of H. pylori 15 . Several studies reported the relationship between H. pylori and the pathogenesis of different upper aerodigestive tract diseases, especially when an induced inflammation was done in the middle ear of mice by inoculating H. pylori whole-cell protein lysate 16 . These findings raised the question whether H. pylori play a causative role in OME.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted on otitis media with effusion and on its correlation with H. pylori ( 15 , 17 - 19 ). However, the correlation between chronic suppurative otitis media and its various aspects, such as tympanosclerosis in which deposition of acellular hyaline and calcified deposits accumulate in the lamina propria of the middle ear has not been sufficiently studied ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%